THE The Effect Of Promotion And Price On Purchase Decisions In Ayam Kremes Pramban Wahidin Medan - Novita laia; Lim, Alvera (Outline Journal of Management and Accounting, 2023)
Consumer decision or purchasing decision is a consumer's final decision in buying a product, both goods and services, after going through certain considerations. Price is very important in the consumer decision-making process because if the product is too expensive and exceeds the consumer's financial ability, it will reduce the target market. The results shows that the test for each variable has a Cronbach's alpha value greater than 0,700 which proves that the questions from all the variables in this study are all reliable and can be used in this research.